2007
DOI: 10.1002/biot.200700097
|View full text |Cite
|
Sign up to set email alerts
|

Mung bean lipoxygenase in the production of a C6‐aldehyde. Natural green‐note flavor generation via biotransformation

Abstract: Mung bean was investigated as a novel source of lipoxygenase in the natural production of the green-note aroma compound hexanal. Lipoxygenase extracted from mung bean catalyzed the oxidative reaction of linoleic acid, after which the intermediate hydroperoxide compound was split via green bell pepper hydroperoxide lyase to produce hexanal. In comparison to soybean lipoxygenase, mung bean lipoxygenase was found to be a good substitute as it produced 15.4 mM (76% yield) hexanal while soybean gave 60% yield. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Legumes are inexpensive source of LOX proteins and particularly high level of LOX activities were identified from various legume seeds (Rao et al 1998). Mung bean was identified as a novel source of LOX in the natural production of green-note aroma compound, hexanal, it is also considered as a cheap and readily available staple food in Asia (Chow et al 2007). Further, mung bean and its seedlings have been used as a source of hydroperoxide lyase enzyme (Rehbock et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Legumes are inexpensive source of LOX proteins and particularly high level of LOX activities were identified from various legume seeds (Rao et al 1998). Mung bean was identified as a novel source of LOX in the natural production of green-note aroma compound, hexanal, it is also considered as a cheap and readily available staple food in Asia (Chow et al 2007). Further, mung bean and its seedlings have been used as a source of hydroperoxide lyase enzyme (Rehbock et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Given that FvJAZ12 functions in the regulation of flavor metabolisms and defense responses (Figures 4, 7), we further explored the signaling cascade upstream of the key enzymes involved in the regulation of flavor metabolism and defense responses. Several studies reported that lipoxygenases may play an important role in either flavor metabolism or defense responses (Suzuki et al, 1999; Fukushige and Hildebrand, 2005; Chow et al, 2007; Reddy et al, 2015; Suzuki et al, 2015). Moreover, our data showed that the expression of FvLOX3 , a gene encoding lipoxygenase, was downstream of FvJAZ12 4A (Figure 7B).…”
Section: Resultsmentioning
confidence: 99%
“…[110] The "pear ester" ( 93) is then obtained by Horner-Wadsworth-Emmons reaction with the phosphonate 89 and (Z)-selective Lindlar reduction of the resulting product 90. [110] Hexanal (48), available sustainably from linoleic acid [111,112,113] (cf. Scheme 7) is the starting material for several alternative routes to 93.…”
Section: Pears For Paradisementioning
confidence: 99%